2021
DOI: 10.1021/acs.orglett.1c03626
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric α-Functionalization of 2-Alkyl Azaarenes: Synthesis of Tertiary Fluorides Having Vicinal Stereogenic Centers

Abstract: An enantioselective approach for synthesizing fluorinated azaarenes containing vicinal quaternary−tertiary stereocenters is summarized. The chiral copper(I)−phosphine complex binds with the azaarenes followed by Michael addition to unsaturated acyl imidazoles, resulting in α-functionalized products with an excellent level of enantioselectivities (up to 99%), diastereoselectivities (>20:1), and yields (up to 97%). Furthermore, post-functionalization of the acyl imidazole part has also been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Subsequently, the effects of solvent on the enantioselectivity of 3 aa were also investigated. Solvent screening revealed that the outcomes in DCM, DCE, THF and toluene were inferior compared to CHCl 3 (Table 1, entries [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the effects of solvent on the enantioselectivity of 3 aa were also investigated. Solvent screening revealed that the outcomes in DCM, DCE, THF and toluene were inferior compared to CHCl 3 (Table 1, entries [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…[12] As a result, novel enantioselective approaches have been devised by employing α,β-unsaturated 2acyl imidazoles as a favored substrate. [13] In this context, our research group recently described enantioselective reports on α,β-unsaturated 2-acyl imidazoles to generate vicinal stereocenters, [14] and to synthesize different core moieties such as substituted pyrrolidines, [15] and 1-pyrrolines. [16] Herein, we disclose the first Sc(III)-pybox catalyzed enantioselective vinylogous Mukaiyama-Michael reaction (VMMcR) of vinyl ketene silyl acetals with α,β-unsaturated 2-acyl imidazoles to construct enantioenriched 1,7-dioxo compounds (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the conjugate addition reactions of organoboron compounds to α,β-unsaturated carbonyl compounds have been successfully achieved, using transition metal catalysts, such as rhodium, palladium, copper, nickel, and so on, which offer a broad substrate scope and functional group tolerance . α,β-Unsaturated 2-acyl imidazoles represent an important class of substrates for asymmetric reactions, and the 2-acylimidazolyl moiety can be transformed into various carboxylic functional groups . In 2012, Ohmiya and Sawamura reported the first enantioselective conjugate addition of alkylboranes (alkyl-9-BBN) to imidazole-2-yl α,β-unsaturated ketones catalyzed by a copper- N -heterocyclic carbene complex (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…7 Addi-tionally, Singh and co-workers also reported a highly enantioselective method for the synthesis of tertiary fluorides bearing vicinal quaternary−tertiary stereocenters. 8 These approaches suggest that the construction of tertiary alkyl fluorides with high enantioselectivity can be efficiently accomplished with α-fluoro pyridinyl acetates. However, in all of the examples, products were furnished with two chiral vicinal stereocenters using identical ligand L1 (Scheme 1, 1a− 1c).…”
mentioning
confidence: 99%
“…Afterward, He and co-workers reported Pd- and Cu-catalyzed asymmetric cross-coupling of conjugated enyne with α-fluoro pyridinyl acetates, giving allenes bearing carbon–fluorine quaternary stereogenic centers in high yield with high enantioselectivities and diastereoselectivities . Additionally, Singh and co-workers also reported a highly enantioselective method for the synthesis of tertiary fluorides bearing vicinal quaternary–tertiary stereocenters . These approaches suggest that the construction of tertiary alkyl fluorides with high enantioselectivity can be efficiently accomplished with α-fluoro pyridinyl acetates.…”
mentioning
confidence: 99%